PREVALENCE OF HAPPINESS AMONG THE POST GRADUATE STUDENTS OF MAHAPURUSHA SRIMANTA SANKARADEVA VISWAVIDYALAYA, NAGAON CAMPUS - Sarma, Mrigakshi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The statement of the present study is, “Prevalence of Happiness Among the Post Graduate Students of Mahapurusha Srimanta Sankaradeva Viswavidyalaya, Nagaon Campus.” Based on the problems of the study the objectives framed are: (i) To develop a Happiness tool for Post Graduate Student. (ii)To study the Prevalence of Happiness among the Post Graduate Students of Mahapurusha Srimanta Sankaradeva Viswavidyalaya. (iii)To find the significant relationship between the Happiness of Male and Female Post Graduate Student from Mahapurusha Srimanta Sankaradeva Viswavidyalaya, Nagaon. In the present study Descriptive survey method is used as it aims to systematically and accurately describe a population and situation or phenomenon. It is an appropriate choice when the aim of the research is to identify characteristics, frequencies, trends, correlation and categories. Simple Random Sampling technique is used to collect the data from 268 samples. The result found that there is no significant difference between the Happiness of Male and Female Post Graduate Students from Mahapurusha Srimanta Sankaradeva Viswavidyalaya, Nagaon.